Systemic Reflections on Knowledge Transfer; Comment on "Sustaining Knowledge Translation Practices: A Critical Interpretive Synthesis" - Joachim P. Sturmberg (Kerman University of Medical Sciences, 2023)
The systemic failure of organisational learning should not come as a surprise - after all every system delivers exactly what it is designed for. Knowledge management/transfer is a property of the organisational system rather than a particular technique. Hence, knowledge management/transfer is about the contextual framing in which learning focused on understanding can occur. Looking through a system lens any research field can be defined as a complex adaptive organisation, and its culture determines if and how learning and knowledge transfer (or shared learning) can occur. Creating and maintain a learning culture requires leadership that perpetuates continuous dialogues to achieve tacit and explicit knowledge exchange.